AI Integration in Literature Review Writing Among Fyp Students: Enhancing Efficiency While Maintaining Academic Integrity - Engku Muhammad Syafiq Engku Safruddin; Fariza Puteh Behak; Noor Saazai Mat Saad; Rahimah Saimin; Suzanah Selamat; Saiful Izwan Zainal (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia